Dengue model with early-life stage of vectors and age-structure within host - Sánchez, Fabio (2019)
We construct an epidemic model for the transmission of dengue fever with an early-life stage in the vector dynamics and age-structure within hosts. The early-life stage of the vector is modeled via a general function that supports multiple vector densities. The basic reproductive number and vector demographic threshold are computed to study the local and global stability of the infection-free state. A numerical framework is implemented and simulations are performed.